(untitled) (Journal of the College of Basic Education, 2024)
The aim of this sine qua non study was to know about the effectiveness of a narrative program in order to develop the child’s self confidence as well as to acquaint the differences in the level of self-confidence depending on sex variable.The researcher used the semi-experimental method. The study was applied to a sample consisting of 60 children aged between 4 and 5 years studied in the preparatory class in the primary stage, they were divided into a control and experimental group on the light of a narrative program.The self-confidence of both groups was measured via statistical analysis package (SPSS).The study reached the following results: -There is an impact of the narrative program on the development of self- confidence in the children of the pilot group. -There are not differences in the level of self-confidence depending on the sex variable in the experimental group.